2010
DOI: 10.1021/ja101603n
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Partitioning of Anions in Lysozyme Dispersions

Abstract: An aqueous dispersion of lysozyme and sodium dodecyl sulfate phase separates below the cloud point. Two liquid phases are formed. At pH < pI electrolytes change the cloud point temperatures (T(c)). These follow an inverse Hofmeister series. Anions partition asymmetrically between the two phases. At fixed cation, the partitioning depends on the specific anion. In a system of finite volume, a concentrated dispersion of a protein is able to act as a chemical "sponge". No active pump is necessary to maintain conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 70 publications
0
52
0
Order By: Relevance
“…Revisiting the problem recently, two of us showed that in a finite volume system ion specific partitioning did occur [46,119].…”
Section: Discussionmentioning
confidence: 99%
“…Revisiting the problem recently, two of us showed that in a finite volume system ion specific partitioning did occur [46,119].…”
Section: Discussionmentioning
confidence: 99%
“…Unless otherwise stated, all potentials reported here are referenced to the SHE (E°' SHE = E°' Ag/AgCl + 0.204 V at 20 °C). The working electrode was placed in the second compartment, which was 25 comprised of a 10 mL cell with a heating jacket connected to a water bath (Lauda ecoline003). Each value of E°' represents an average of 3 ± 1 data points.…”
Section: Methodsmentioning
confidence: 99%
“…Specific ion effects were examined at 25 an ionic concentration of 200 mM, a concentration reasonably close to that where specific ion effects are observed but sufficiently low to provide an observable faradaic response. Plots of peak current for a range of anions (Fig.…”
Section: Specific Ion Effects On Peak Current Of Cyt Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though they are ubiquitous in the physical, chemical and biological literature, their origin is still contested 1-7 and has been recently brought to the forefront of research [8][9][10][11][12][13][14][15][16][17][18][19] . New work in this area may break down barriers between physics and biology 9 .…”
mentioning
confidence: 99%